Evaluation The Laser Effects on Phage of Acentobacter Bumanii Isolated from Clinical Samples in Iraq/Qadisyiah - Alwan, Merriam Ghadhanfar; Abood, Noor Adil; Taha, Sarah K.; Faja, Orooba Meteab; tarek, Lina zeyad; Kadhim, Haider Sabah; Alkhozai, Ziad M. (Journal of Pharmacology and Drug Development, 2025)
Objective: Acinetobacter baumannii is a pathogenic bacterium with clinical attributes of nosocomial infection and resistance to antibiotics. Phage therapy represents a potential solution because it can specifically target MDR strains. This study aimed to isolate and characterize a lytic bacteriophage specific to A. baumannii, evaluate its kinetic and lytic properties, and investigate the effects of laser treatment on enhancing phage antibacterial activity against multidrug-resistant clinical isolates. Methods: Clinical specimens were collected from patients in three hospitals in Al-Diwaniyah, Iraq, and A. baumannii isolates were identified using standard biochemical tests, API systems, and 16S rRNA PCR sequencing. Environmental samples were screened to isolate lytic phages, which were propagated, purified, and analyzed using plaque assays and scanning electron microscopy. Phage kinetics—including adsorption rate, eclipse period, lysis time, and burst size—were assessed using standard bacteriophage quantification methods. Laser treatment was applied to evaluate its effect on phage activity under different temperatures and pH conditions. Results: A lytic phage specific to A. baumannii was successfully isolated, exhibiting an icosahedral head and a long tail typical of virulent phages. The phage showed rapid adsorption, a short eclipse period, and a high burst size ( 111 phages per infected cell). It demonstrated strong lytic activity at temperatures between 35–45 °C and pH 8–10.5. Laser exposure, at 250 pulses, significantly enhanced phage antibacterial activity, resulting in faster bacterial lysis and increased phage productivity. Conclusions: The combination of phage therapy and laser treatment represents a promising strategy for combating MDR A. baumannii